Cardiac sympathetic innervation, from a different point of (re)view. (15th June 2017) - Zaglia, Tania; Mongillo, Marco
Abstract : The cardiac sympathetic nervous system continuously controls heart function, by integrating inputs from environmental and intrinsic stimuli, including stresses and emotions (CNS, top box), relayed to the heart through the postganglionic effector neurons which originate from the sympathetic ganglia chain (cSNS, bottom box). The heart is densely innervated by sympathetic neurons, whose processes lay on CMs, establishing multiple discrete neuro‐cardiac contacts in correspondence to neurotransmitter releasing sites (middle box, enlarged). Recent work reviewed here supports the concept that the specific molecular organization of the neuro‐cardiac junctions (right box) allows signal transmission between neurons and cardiac effector cells to operate in a quasi‐synaptic behaviour. Abstract: The audience of basic and clinical scientists is familiar with the notion that the sympathetic nervous system controls heart function during stresses. However, evidence indicates that the neurogenic control of the heart spans from the maintenance of housekeeping functions in resting conditions to the recruitment of maximal performance, in the fight‐or‐flight responses, across a whole range of intermediate states. To perform such sophisticated functions, sympathetic ganglia integrate both peripheral and central inputs, and transmit information to the heart via 'motor' neurons, directly interacting with target cardiomyocytes. To date, the dynamics and mode of communication between these two cell types, which determine how neuronal information is adequately translated into the wide spectrum of cardiac responses, are still blurry. By combining the anatomical and structural information brought to light by recent imaging technologies and the functional evidence in cellular systems, we focus on the interface between neurons and cardiomyocytes, and advocate the existence of a specific 'neuro‐cardiac junction', where sympathetic neurotransmission occurs in a 'quasi‐synaptic' way. The properties of such junctional‐type communication fit well with those of the physiological responses elicited by the cardiac sympathetic nervous system, and explain its ability to tune heart function with precision, specificity and elevated temporal resolution.